Descriptive Memoir of Ministry of Labour as on 1st December 1955 Government of India - Planning Commission (Planning Commission, 1955)
The Ministry is mainly concerned with subjects like welfare of labour trade unions, industrial and labour dispute., factory labour, unemployment insurance, health insurance, which appear in the Union end Concurrent Lists of the Seventh Schedule of the Constitution of India. The Central Government is responsible only for laying down policy for the whole of India in such matters, while the implementation of the policy is the responsibility of the State Governments concerned subject to the control and direction of the Central Government. In respect of the labour employed in railways major ports, mines and oil-fields appearing in the Union List, however, the Centre carries full responsibility.
Government of India Cabinet Secretariat [O and M Division]